An ambipolar organic field-effect transistor based on an AIE-active single crystal with a high mobility level of 2.0 cm2 V−1 s−1. Issue 11 (5th January 2016) - Deng, Jian; Xu, Yuanxiang; Liu, Liqun; Feng, Cunfang; Tang, Jia; Gao, Yu; Wang, Yan; Yang, Bing; Lu, Ping; Yang, Wensheng; Ma, Yuguang
Abstract : Ambipolar OFETs based on AIE-active materials were demonstrated to have a high and balanced mobility level of 2.0 cm 2 V −1 s −1 . Abstract : Organic field-effect transistors (OFETs) based on an aggregation-induced emission (AIE) material were fabricated using a calcium–gold asymmetric electrode system. The devices showed very high and balanced mobility, reaching 2.50 and 2.10 cm 2 V −1 s −1, respectively, for electron and hole. Strong green electroluminescence from the single-crystal side edge was observed from all the devices. This work demonstrates that AIE active materials could not only achieve high luminescence, but also be used in light emitting transistors and achieve very high mobility.